The Urgency of Non-Formal Islamic Education (Madrasah Diniyah) - Muhammad Faiq Hirzulloh (Social Science Academic, 2024)
This study aims to describe the urgency of non-formal Islamic education in this case madrasah diniyah as an Islamic religious education institution to build future generations. Religious education in madrasah diniyah includes the education of belief, worship, and morals. Therefore, diniyah has a very important role and responds to various crises, especially spiritual crises, faced by modern society today. The research method is qualitative research from several madrasah diniyah through interviews, observation, and documentation in Madiun Regency, East Java in general. The results of this study indicate that the religious aspects of society will be greatly influenced by the existence of madrasah diniyah so that in the future it will become a generation of insan kamil that can be used to act in life. Islamic education in madrasah diniyah is the process of transformation and internalization of knowledge and values of religious education through guidance, direction, teaching, in spiritual growth in accordance with Islamic teachings. madrasah diniyah has several objectives of Islamic education as follows: 1). Providing religious knowledge starting from childhood; 2). Preparing children as the next generation; 3). Creating children to become insan kamil; 4). Planting Religious Education Values; 5). Improving the learning of religious education in formal schools; and 6). Growing Public Attention to Religious Education.